2021
DOI: 10.3889/oamjms.2021.6980
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Insulin Gene Expression with CRISPR/Cas9-based Transcription Factors

Abstract: Background: The discovery and use of CRISPR/Cas9 technology have enabled researchers throughout the globe to continuously edit genomes for the benefit of science and medicine. Diabetes type I is one field of medicine where CRISPR/Cas9 has a strong potential for cell therapy development. The long-lasting paucity of healthy cells for clinical transplantation into diabetic patients has led to the search of new methods for producing β-cells from other human cell types. Embryonic stem cells are being studied worldw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Interleukin 10, an anti-inflammatory cytokine, has been shown to reduce autoimmune damage to β-cells and enhance the resilience of stem cells as part of the immune system of recipients after transplantation. Additionally, in 2021, Alzhanuly et al demonstrated the application of CRISPR-Cas9 technology in human cells to modulate insulin production (43).…”
Section: Gene Editingmentioning
confidence: 99%
“…Interleukin 10, an anti-inflammatory cytokine, has been shown to reduce autoimmune damage to β-cells and enhance the resilience of stem cells as part of the immune system of recipients after transplantation. Additionally, in 2021, Alzhanuly et al demonstrated the application of CRISPR-Cas9 technology in human cells to modulate insulin production (43).…”
Section: Gene Editingmentioning
confidence: 99%
“…The most active among these factors were found to be pancreatic and duodenal homeobox 1 (PDx1), protoendocrine factor (neurogenin 3, Ngn3), NK6 homeobox 1 (NKx6.1), and musculoaponeurotic fibrosarcoma oncogene family A (MaFA). In further experiments, the possibility of manipulating insulin production in HEK293 cells was demonstrated through the artificial activation of the INS insulin gene with CRISPR/dCas9-based transcription factors [249]. The stimulation of the insulin production has been achieved in pancreatic β-cell genes through the multiplex activation of PDX1, NEUROG3, PAX4, and INS genes using CRISPR/dCas9-VP160, CRISPR/dCas9-TET1 and CRISPR/dCas9-P300 epigenetic activators [250].…”
Section: Crispr/cas9 Artificial Transcription Factorsmentioning
confidence: 99%
“…Metabolic controllers based on induced protein degradation have the potential to overcome issues related to the accumulation of inhibitory or toxic intermediates and the heterogeneity of cellular states and environments by preventing accumulation of causal enzymes through negative feedback control. Protein degradation systems offer the advantage of transcriptional independence over other exogenous approaches for modulating protein activity, such as transcriptional repression [138], RNAi [139,140], CRISPR/Cas9 and/or dCas9 [141,142], toggle switches [139,143]. Knocking out, silencing, or turning off protein-encoding genes often disrupts cognate genes, leading to slow growth phenotypes and deleterious effects on cell metabolism [135].…”
Section: Biosensors For Controlling Cellular Protein Abundance and Me...mentioning
confidence: 99%